Pengembangan Potensi Joglo dan Gamelan sebagai Tujuan Wisata Budaya - Rela Adi Himarosa; Cahyo Setiadi Ramadhan; Evy Yulianti (Universitas Mathla'ul Anwar Banten, 2019)
POTENTIAL EXPANSION OF JOGLO AND GAMELAN AS CULTURAL TOURISM DESTINATIONS. Joglo is one of the heritage forms of traditional Javanese houses in Yogyakarta, as well as traditional Gamelan musical instruments. The former Head of the Gilangharjo Village Jetis, Gilangharjo, Pandak, Bantul opened a Joglo with a set of Gamelan music equipment. Joglo has been approved as a cultural heritage building by the DIY Provincial Government. Even though Joglo has become a cultural heritage building, the potency for cultural heritage houses and Gamelan musical instruments are underutilized by residents. The development of Joglo cultural tourism and Gamelan will run well by involving the village community. This service aims to empower the community to increase the potency of Joglo and Gamelan to become cultural tourism destination and become community-based tourism. The purpose of this service are to participate by involving the village community involved in tourism development and starting to become known as the Joglo location and Gamelan arts in Jetis Village. The results of this service consist of profiles of Joglo websites and videos. Utilizing the advances in information technology and social media, the more popular Joglo in Jetis RT 03.